Improving Financial Literacy and Economic Performance of Farmer Groups through the Adoption of Sorghum Processing Technology in Pekan Tanjung Beringin Village - Rafida Khairani; Khasrad; Herlin Munthe; Purnama Yanti Purba; Armansyah; Rusdimansyah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This community service activity aims to improve the financial literacy and economic performance of farmer groups through the adoption of sorghum processing technology in Pekan Tanjung Beringin Village, Serdang Bedagai Regency. This program is motivated by the low understanding of farmer groups related to business management, agricultural product processing, digital marketing, and the use of appropriate technology in supporting the increase in productivity and income of village communities. The implementation method is carried out through a community empowerment approach based on workshops, training, mentoring, and technology transfer. Activities include training in sorghum cultivation and processing, financial literacy, digital marketing, and the provision of sorghum processing technology such as soil tillage tools, threshers, flouring tools, and sorghum waste processing tools. This activity was also accompanied by experts from Andalas University and involved students as an implementation of the Independent Learning Independent Campus (MBKM) program. The results of the activity showed an increase in the understanding and skills of farmer groups in sorghum processing, the use of appropriate technology, business management, and the marketing of digital-based products. This program is expected to be able to increase productivity, add value of agricultural products, and strengthen the economic independence of village communities in a sustainable manner.